REKONSTRUKSI MASKULINITAS: MENGUAK PERAN LAKI-LAKI DALAM PERJUANGAN KESETARAAN GENDER - Gusri Wandi (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Gender inequality is a phenomenon that is still sticking to the present. To overcome the various programs have been implemented for the sake of equality. But it is still fixed in women, while men who also had a big hand in the creation of these gaps are rarely involved. How important is the role of men in gender equality and how to realize them? This question will be discussed in this paper.